Association between serum uric acid level and renal arteriolar hyalinization in individuals without chronic kidney disease. (November 2017) - Matsukuma, Yuta; Masutani, Kosuke; Tanaka, Shigeru; Tsuchimoto, Akihiro; Haruyama, Naoki; Okabe, Yasuhiro; Nakamura, Masafumi; Tsuruya, Kazuhiko; Kitazono, Takanari
Abstract: Background and aims: Recent studies have reported an association between serum uric acid (SUA) and renal arteriolar changes in patients with chronic kidney disease (CKD). However, the association in individuals without CKD remains unclear. In this study, we investigated the relationship between SUA and renal arteriolar lesions in individuals without CKD from our living kidney donor cohort. Methods: Between January 2006 and May 2016, 393 living kidney donors underwent "time-zero" biopsy at Kyushu University Hospital. Patients were divided into sex-specific quartiles of SUA before donation: Q1, Q2, Q3, and Q4 (male: <5.2, 5.2–5.8, 5.9–6.4, and ≥6.5 mg/dL, female: <3.8, 3.8–4.3, 4.4–5.0, and ≥5.1 mg/dL). Renal arteriolar hyalinization and wall thickening were assessed using a semiquantitative grading system. Predictive performance was compared between models with and without SUA by calculating the net reclassification improvement (NRI). Results: In total, 158 (40.2%) patients had arteriolar hyalinization, and 148 (37.6%) had wall thickening. High SUA was significantly associated with arteriolar hyalinization in multivariable logistic analysis (odds ratio [OR] per 1-mg/dL increase in SUA, 1.24; 95% confidence interval [CI], 1.00–1.53; p  = 0.048. OR for Q4 vs. Q2, 2.22; 95% CI, 1.17–4.21; p  = 0.01). We found no association between SUA and wall thickening. When SUA was incorporated into a predictive model with conventional atherosclerotic factors, the NRI was 0.21 ( p  = 0.04). Conclusions: High SUA was an independent risk factor for arteriolar hyalinization in individuals without CKD. SUA provided additional predictive value beyond conventional atherosclerotic factors in predicting arteriolar hyalinization. Highlights: An association between serum uric acid and renal arteriolar changes is unclear. We examined the relationship in individuals without CKD using a living donor cohort. High serum uric acid was an independent risk factor for arteriolar hyalinization.